A black adrenal adenoma with high FDG uptake on PET/CT scan in a patient with esophageal carcinoma: A case report. (2018) - Matsumoto, Shiro; Hosoya, Yoshinori; Lefor, Alan Kawarai; Haruta, Hidenori; Ui, Takashi; Kurashina, Kentaro; Saito, Shin; Ashizawa, Kentaro; Sasaki, Takahiro; Kitayama, Joji; Sata, Naohiro
Highlights: Black adrenal adenoma (BAA) is a rare benign adrenal lesion. Most adrenal tumors with high uptake on positron emission tomography (PET) scan are malignant, but the benign BAA is also positive on PET scan. This is the first report of a patient with esophageal cancer and BAA, emphasizing the importance of differentiating BAA from metastatic disease. Abstract: Introduction: Black adrenal adenoma (BAA) is a rare, benign adrenal lesion with a black or brown appearance. This is the first report of this lesion in a patient with a synchronous esophageal cancer and highlights the importance of considering a false positive finding on a Positron Emission Tomography (PET) scan, which might otherwise preclude resection. Presentation of case: A 73-year-old male was diagnosed with mid-esophagus carcinoma. Computed tomography scan revealed an enlarged left adrenal gland. Plasma adrenocorticotropic hormones levels were normal. To characterize the adrenal lesion, a PET scan was obtained which showed high uptake of 18 F-fluoro-2-deoxy-d -glucose (FDG), consistent with a metastasis, suggesting T3N2M1, clinical stage IV esophageal cancer. After two courses of neo-adjuvant therapy, sub-total esophagectomy and left adrenalectomy were performed. The adrenal tumor was soft, and black in color, diagnosed as a BAA on histology. The pathologic stage of the esophageal cancer was T3N0M0, Stage II. Six months after surgery, he is alive without recurrence. Discussion: High FDG uptake by an adrenal lesion on PET scan, as in this patient, usually suggests a metastatic lesion. Although rare, patients with esophageal cancer and adrenal metastases have been reported to have long-term survival, so it is important to characterize an adrenal lesion when found. Conclusion: Most adrenal lesions with high FDG uptake are malignant, but BAA is also positive on PET scan. Although rare, BAA should be considered in patients with solitary adrenal lesions with high uptake on PET scan, even in the presence of a malignancy.